ANALISIS KEBIJAKAN PENGENDALIAN PELAKU HOAX DAN UJARAN KEBENCIAN - Lubis, Fauziah (PERSPEKTIF, 2020)
This study aims to review and analyze the policy of controlling fake news or hoaxes and expressions of hatred based on Law Number 11 which has been changed to Act Number 19 of 2016 concerning Information and Electronic Transctions as well as several other provisions. This research method is a qualitative research method by analyzing a statutory regulation. Besides that, it also examines the sources of textbooks, journal books in the library to support data and information in analyzing. The results of this study indicate that the basic policy regarding the dissemination of false news or hoaxes and hate speech that has been regulated in Law Number 19 Year 2016 article 28 paragraphs 1 and 2 has been effective because it can limit the space for the perpetrators of hoaks and hate speech. More specifically, the perpetrators can be charged with other related articles namely article 311 and 378 of the Criminal Code, Article 27 paragraph 3 of Law Number 19 of 2016 concerning Information and Electronic Transactions, Law No. 40 of 2008 concerning the Elimination of Racial and Ethnic Discrimination, as well as the perpetrators of spreading false news may also be subject to articles related to hate speech. Besides that, the more rapid and development of digital technology today, the more diverse the new crimes committed through this digital media, in this case the spread of false news (Hoax) that is rife. As many as 800,000 sites in Indonesia have been indicated as spreading false information.